2020
DOI: 10.1111/ina.12677
|View full text |Cite
|
Sign up to set email alerts
|

Associations between respiratory infections and bacterial microbiome in student dormitories in Northern China

Abstract: Recent studies reveal that the microbial diversity and composition in the respiratory tract are related to the susceptibility, development, and progression of respiratory infections. Indoor microorganisms can transmit into the respiratory tract through breathing, but their role in infections is unclear. Here, we present the first association study between the indoor microbiome and respiratory infections. In total, 357 students living in 86 dormitory rooms in Shanxi University were randomly selected to survey s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The bacterial composition in Shanxi high schools was more similar to the air and human skin microbiomes than to the soil, freshwater, human gut and saliva microbiomes (calculated from the Earth Microbiome Project [ 41 ]). Additionally, some high-abundance bacterial genera in Shanxi high schools were also present in high abundance in other indoor environments such as the dormitories of Shanxi University, China and junior high school classrooms in Malaysia [ 12 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial composition in Shanxi high schools was more similar to the air and human skin microbiomes than to the soil, freshwater, human gut and saliva microbiomes (calculated from the Earth Microbiome Project [ 41 ]). Additionally, some high-abundance bacterial genera in Shanxi high schools were also present in high abundance in other indoor environments such as the dormitories of Shanxi University, China and junior high school classrooms in Malaysia [ 12 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial abundance in air, non-saline soil and freshwater, and the human gut, saliva and skin environment were calculated from the Earth Microbiome Project [ 41 ]. The bacterial abundance in the university dormitory and junior high school was calculated from two recent publications [ 12 , 42 ]. Taxa with relative abundance > 0.1% were formatted with bold font Taxa High school (%) Air (%) Soil (%) Water (%) Human gut (%) Human saliva (%) Human skin (%) University dormitory, China (%) Junior high school, Malaysia (%) Psychrobacter 5.36 0.12 < 0.01 0.01 0 < 0.01 0.18 0.04 0 Kocuria 3.82 < 0.01 < 0.01 < 0.01 < 0.01 0.02 0.43 0.25 1.43 Brachybacterium 3.41 0.16 0.02 < 0.01 0.03 < 0.01 0.59 0.23 0.71 Micrococcus 3.22 0.10 < 0.01 < 0.01 < 0.01 < 0.01 0.65 0.54 0.82 Acinetobacter 2.99 2.30 0.10 1.37 0.02 0.21 4.93 23.2 2.21 Microbacterium 2.93 0.03 0.10 0.06 < 0.01 < 0.01 0.03 0.75 0 Paracoccus 2.80 0.18 0.01 ...…”
Section: Resultsmentioning
confidence: 99%
“…Two earlier studies on indoor microbiota in university dormitories in North-China explored associations of indoor microbiota characteristics with having a plant in the room or not and found significantly higher bacterial richness in floor dust, but not airborne settled dust, for dormitories with one or more plants. 31,32 No significant differences in bacterial community composition (beta-diversity) were reported in these studies. In contrast to the positive associations with indoor microbial diversity, we did not observe any significant relationship between the bacterial and fungal load measures, i.e.…”
Section: Our Primary Finding Was the Increase In Bacterial And Fungalmentioning
confidence: 68%
“…Furthermore, their leaves are in constant exchange with the atmosphere, and their root‐associated microbes have environmental degrading properties 27‐30 . There is, however, a lack of studies investigating the contribution of indoor plants to the indoor microbial content, and the few available studies focus on experimental research, closed, and specialized high‐density environments 19,20,31,32 . Thus, more comprehensive research is required, in particular, including designs representing various real‐life conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential protective effects of childhood infections are suggested to relate to the training and maturation of the immune system from the exposure 58 . A recent study in university dormitories reported that exposed to facultative pathogens, including Haemophilus , Klebsiella ,Buttiauxella , and Raoultella , increased the odds of having respiratory infections 61 . Overall, more studies are needed to verify the pattern we observed in this study and further disentangle the health effects of the indoor microbiome on different respiratory diseases.…”
Section: Health Effects Of the Microbial Speciesmentioning
confidence: 99%